2022
DOI: 10.1039/d2cp00494a
|View full text |Cite
|
Sign up to set email alerts
|

Transient changes in aromaticity and their effect on excited-state proton transfer reactions

Abstract: Quantum chemical modelling shows that energy barriers for excited-state proton transfer reactions involving 2-pyridone are governed by the transient onset of antiaromaticity upon interaction between the photoexcited state and a second excited state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Interestingly, in the S 2 state the benzene ring was found to be aromatic, and as a result, the ESIPT process in this state is unfavorable (Figure 22). [186] At this point it should be stressed that it has been concluded that by considering only the (anti‐)aromatic character of excited‐state reactants and products in ESPT reactions one may neglect important (anti‐)aromaticity effects along the reaction paths which are decisive [188] . This is especially critical when there is an interaction between two electronically excited states.…”
Section: Relief Of Esaamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the S 2 state the benzene ring was found to be aromatic, and as a result, the ESIPT process in this state is unfavorable (Figure 22). [186] At this point it should be stressed that it has been concluded that by considering only the (anti‐)aromatic character of excited‐state reactants and products in ESPT reactions one may neglect important (anti‐)aromaticity effects along the reaction paths which are decisive [188] . This is especially critical when there is an interaction between two electronically excited states.…”
Section: Relief Of Esaamentioning
confidence: 99%
“…The connection between ESIPT processes and ESAA relief was explored computationally in salicylic acid and 2‐(2’‐hydroxyphenyl)benzoxazole (HBO) derivatives [185–188] . Lampkin et al.…”
Section: Relief Of Esaamentioning
confidence: 99%
“…[39,40] It is thus plausible that excited-state (anti)aromaticity modulates the height of the activation barriers of the retro-aldol reaction in 3 BPT. In fact, NICS-scans [41,42] (nucleus-independent chemical shift) on the pyrazine subunit of the pterin chromophore register a decrease of antiaromaticity along the 3 BPT! 3 I2 retroaldol reaction coordinate (Section 5.2 of the Supporting Information).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…However, already in 1972, following earlier work by Dewar 25 and Zimmerman, 26 the concepts of excitedstate aromaticity (ESA) and antiaromaticity (ESAA) [27][28][29][30][31] were given a solid theoretical foundation through the discovery by Baird 32 that annulenes with 4n and 4n + 2 p-electrons are respectively aromatic and 5 (20) antiaromatic in their lowest triplet pp* excited state (T1), thus implying a reversal of (anti)aromatic character in this state relative to the ground state as asserted by Hückel's rule. With time, and particularly since the past decade or so, 33,34 ESA and ESAA have established themselves as very useful concepts for explaining and predicting photophysical properties [35][36][37][38] and photochemical reactivities [39][40][41][42][43][44][45][46][47][48][49][50][51][52] of both triplet and singlet excited states of organic molecules.…”
mentioning
confidence: 99%
“…In this light, it is of particular interest to establish how the HOMA index performs for excited states, as this index is probably the easiest to calculate, requiring only a quantum-chemical geometry optimization. Indeed, for this reason, HOMA has often been employed to highlight photochemical consequences of ESA and ESAA, [40][41][42]44,45,[48][49][50] despite that it is yet to be parameterized for excited states.…”
mentioning
confidence: 99%